Expectations of Transition-Age Students With Autism Spectrum Disorder Toward Postsecondary Education - Xueqin Qian; Seunghee Lee
The purpose of this study was to examine factors associated with expectations regarding postsecondary education of students with autism spectrum disorder between the ages of 16 and 21 years. We conducted logistic regressions using variables at the student, family, and school levels using the National Longitudinal Transition Study 2012. Logistic regression results showed that parental expectations for attending college was the only significant predictor of students$1 (Bown educational expectations. Students$1 (Badaptive functioning, autonomy levels, demographic and family variables, parent involvement, and prior roles in Individualized Education Program/transition planning were not significant predictors. Future research needs to examine how schools can develop effective ways to increase both students$1 (Band parents$1 (Bexpectations toward postsecondary education.s